Whole Genome Sequencing of the Symbiont Pseudovibrio sp. from the Intertidal Marine Sponge Polymastia penicillus Revealed a Gene Repertoire for Host-Switching Permissive Lifestyle - Alex, Anoop (Genome Biol Evol, 2015)
Sponges harbor a complex consortium of microbial communities living in symbiotic relationship benefiting each other through the integration of metabolites. The mechanisms influencing a successful microbial association with a sponge partner are yet to be fully understood. Here, we sequenced the genome of Pseudovibrio sp. POLY-S9 strain isolated from the intertidal marine sponge Polymastia penicillus sampled from the Atlantic coast of Portugal to identify the genomic features favoring the symbiotic relationship. The draft genome revealed an exceptionally large genome size of 6.6 Mbp compared with the previously reported genomes of the genus Pseudovibrio isolated from a coral and a sponge larva. Our genomic study detected the presence of several biosynthetic gene clusters—polyketide synthase, nonribosomal peptide synthetase and siderophore—affirming the potential ability of the genus Pseudovibrio to produce a wide variety of metabolic compounds. Moreover, we identified a repertoire of genes encoding adaptive symbioses factors (eukaryotic-like proteins), such as the ankyrin repeats, tetratrico peptide repeats, and Sel1 repeats that improve the attachment to the eukaryotic hosts and the avoidance of the host’s immune response. The genome also harbored a large number of mobile elements (∼5%) and gene transfer agents, which explains the massive genome expansion and suggests a possible mechanism of horizontal gene transfer. In conclusion, the genome of POLY-S9 exhibited an increase in size, number of mobile DNA, multiple metabolite gene clusters, and secretion systems, likely to influence the genome diversification and the evolvability.